2021
DOI: 10.3390/ijerph182312828
|View full text |Cite
|
Sign up to set email alerts
|

Reassessing Fitness-to-Drive in Drinker Drivers: The Role of Cognition and Personality

Abstract: Drunken driving is among the main challenges for road safety by causing worldwide motor-vehicle crashes with severe injuries and deaths. The reassessment of fitness-to-drive in drivers stopped for drunken driving includes mainly psychological examinations. The present study aimed to investigate the effectiveness and the consistency of selected variables of different psychological driving-related dimensions (i.e., cognitive skills and personality) in discriminating 90 male drinker drivers (DD) from matched non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 90 publications
0
5
0
Order By: Relevance
“…One potential explanation for the link between learning to drive and navigation ability is that those people who learn earlier have greater spatial perspective taking, mental rotation and visuospatial processing ability which lead to being able to learn to drive faster and learning to navigate better. This is supported by evidence that better performance on different facets of spatial cognition are associated with better driving performance (Andrews & Westerman, 2012; Di Meco et al, 2021; Kunishige et al, 2020; Moran et al, 2020; Tinella et al, 2020, 2021a, 2021b) and navigation ability (Garg et al, 2023; Wolbers and Hegarty, 2010). Indeed, spatial skills can predict driving test success in clinical and non-clinical samples (Barco et al, 2014; Barrash et al, 2010; Crizzle et al, 2012).…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…One potential explanation for the link between learning to drive and navigation ability is that those people who learn earlier have greater spatial perspective taking, mental rotation and visuospatial processing ability which lead to being able to learn to drive faster and learning to navigate better. This is supported by evidence that better performance on different facets of spatial cognition are associated with better driving performance (Andrews & Westerman, 2012; Di Meco et al, 2021; Kunishige et al, 2020; Moran et al, 2020; Tinella et al, 2020, 2021a, 2021b) and navigation ability (Garg et al, 2023; Wolbers and Hegarty, 2010). Indeed, spatial skills can predict driving test success in clinical and non-clinical samples (Barco et al, 2014; Barrash et al, 2010; Crizzle et al, 2012).…”
Section: Discussionmentioning
confidence: 88%
“…Although many studies have shown that specific facets of spatial cognition are associated with driving experience and performance (Andrews & Westerman, 2012; Di Meco et al, 2021; Kunishige et al, 2020; Moran et al, 2020; Tinella et al, 2020, 2021a, 2021b), our study was the first to investigate the relationship between self-reported driving experience and measured wayfinding ability. As hypothesised, we found a significant association between the age one started to drive solo and wayfinding distance, where those who started driving solo below 18 were significantly better at navigating than those who started driving solo aged 18 and above.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Several points have been identified on which psychological sciences can provide input. Cognitive sciences, cognitive neurosciences, neuropsychology, and psychometrics can provide support in the development of training and services that can facilitate (a) the autonomy of individuals from a deeper assessment of available physical and mental resources [38,39,90], (b) comfort [14], the management of (c) the fear of the unfamiliar [13], and of (d) the risk of falls and the fear associated with falls [58], but most importantly can (e) contribute to the psychological training of transport service providers and workers, who will be called upon to recognize the needs of older people and the nature of various factors, including: motor (e.g., appropriate times for getting in and out of cars, avoiding abrupt changes in speed or direction), sensory (e.g., speaking up, making use of large visual aids), psychological (e.g., giving time to ask questions, practicing listening, treating with kindness), technological (e.g., knowing how to use assistive devices for movement). Simultaneously, it is also necessary to envision a redefinition of schedules that will necessarily affect travel times so that the greater commitment required by age-friendly behaviors will not be the sole responsibility of transportation workers.…”
Section: Discussionmentioning
confidence: 99%
“…Even secondary tasks, such as interacting with in-vehicle technologies, can be a distraction source leading to traffic crashes [55]. Additionally, a driver's personality and sociodemographic characteristics can significantly influence the driving behavior and the likelihood of crashes [56].…”
Section: What Does Driving Involve?mentioning
confidence: 99%